A Study of Situational Leadership Style at PT Singosari, Tidung, Rappocini, Makassar City, South Sulawesi, Indonesia. - Jamaluddin; Muliana; Akib, Haedar; Salam, Rudi; Kasmita, Maya; Tenri, Oktamaya (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
Organizational success in achieving goals and objectives depends on the manager and his leadership style. This study aims to describe the effectiveness of the application of the situational leadership style at PT Singosari Timur Jaya Makassar. To achieve this goal, the researcher determined 5 (five) informants with the type of research and the approach used was descriptive qualitative. Collecting data through interview techniques, observation, and documentation. The results showed that the warehouse head of PT Singosari Timur Jaya Makassar was classified as having implemented situational leadership well, with the involvement of the leader in determining and assigning tasks to employees that had been running optimally, implementing relationship behavior with employees well, and the attitude of the leadership in addressing the readiness of followers effectively viewed from the indicators of telling style, selling style, participating style, and delegating style.